Heme oxygenase-independent bilin biosynthesis revealed by a hmox1 suppressor screening in Chlamydomonas reinhardtii - Zhang, Weiqing; Deng, Rui; Shi, Weida; Li, Zheng; Larkin, Robert M.; Fan, Qiuling; Duanmu, Deqiang (Frontiers in Microbiology, 2022)
Bilins are open-chain tetrapyrroles synthesized in phototrophs by successive enzymic reactions catalyzed by heme oxygenases (HMOXs/HOs) and ferredoxin-dependent biliverdin reductases (FDBRs) that typically serve as chromophore cofactors for phytochromes and phycobiliproteins. Chlamydomonas reinhardtii lacks both phycobiliproteins and phytochromes. Nonetheless, the activity and stability of photosystem I (PSI) and the catalytic subunit of magnesium chelatase (MgCh) named CHLH1 are significantly reduced and phototropic growth is significantly attenuated in a hmox1 mutant that is deficient in bilin biosynthesis. Consistent with these findings, previous studies on hmox1 uncovered an essential role for bilins in chloroplast retrograde signaling, maintenance of a functional photosynthetic apparatus, and the direct regulation of chlorophyll biosynthesis. In this study, we generated and screened a collection of insertional mutants in a hmox1 genetic background for suppressor mutants with phototropic growth restored to rates observed in wild type 4A+ C. reinhardtii cells. Here, we characterized a suppressor of hmox1 named ho1su1 with phototrophic growth rates and levels of CHLH1 and PSI proteins that were similar to 4A+. Tetrad analysis indicated that a plasmid insertion co-segregated with the suppressor phenotype of ho1su1. Results from TAIL-PCR and plasmid rescue experiments demonstrated that the plasmid insertion was located in exon 1 of the HMOX1 locus. Heterologous expression of the bilin-binding reporter Nostoc punctiforme NpF2164g5 in the chloroplast of ho1su1 indicated that bilin accumulated in the chloroplast of ho1su1 despite the absence of the HMOX1 protein. Collectively, our study reveals the presence of an alternative bilin biosynthetic pathway independent of HMOX1 in the chloroplasts of Chlamydomonas cells.